2016
DOI: 10.1093/mmy/myw031
|View full text |Cite
|
Sign up to set email alerts
|

Triazole antifungals used for prophylaxis and treatment of invasive fungal disease in adult haematology patients: Trough serum concentrations in relation to outcome

Abstract: Triazole antifungal drugs are widely used for the prophylaxis and treatment of invasive fungal disease (IFD). Efficacy may depend on attaining minimum effective plasma concentrations. The aim of this study was to ascertain the proportion of samples in which the recommended concentrations were achieved in patients given these drugs in relation to outcome. In-patients prescribed standard doses of fluconazole, itraconazole solution, posaconazole suspension, or oral voriconazole for at least one week were studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…When CT of the lungs is non‐conclusive for IFD and biomarkers in blood and/or BAL are negative, mould active prophylaxis may be continued without starting targeted antifungal therapy with a different antifungal agent. Therapeutic drug monitoring is recommended for azoles such as itraconazole, posaconazole or voriconazole to exclude insufficient serum levels of the particular drug . Breakthrough IFD may occur under mould‐active prophylaxis caused by azole‐resistant fungal pathogens .…”
Section: Diagnostic Schedulesmentioning
confidence: 99%
“…When CT of the lungs is non‐conclusive for IFD and biomarkers in blood and/or BAL are negative, mould active prophylaxis may be continued without starting targeted antifungal therapy with a different antifungal agent. Therapeutic drug monitoring is recommended for azoles such as itraconazole, posaconazole or voriconazole to exclude insufficient serum levels of the particular drug . Breakthrough IFD may occur under mould‐active prophylaxis caused by azole‐resistant fungal pathogens .…”
Section: Diagnostic Schedulesmentioning
confidence: 99%
“…These breakthrough IFDs may either due to resistant fungal pathogens (eg Mucor spp.) and/ or low through serum concentration of the triazole 103,110 . A definition for breakthrough IFD has been recently proposed by the Mycoses Study Group Education and Research Consortium (MSG) and the European Confederation of Medical Mycology (ECMM) 111 .…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis also showed a positive correlation between serum albumin concentrations and fluconazole and echinocandin exposures. Nguyen et al [16][17][18][19][20][21][22][23][24][25][26] reported that low serum albumin concentrations in the surgical ICU patients were correlated with low caspofungin exposures. We believe that patients with hypoalbuminemia should be considered a ''high-risk group'' of low antifungal serum exposure who could especially benefit from systematic monitorization of the antifungal concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, systematic therapeutic drug monitoring (TDM) of antifungals is not considered routinely necessary [6], mainly because of the belief that an adequate antifungal serum concentration is usually achieved by prescribing fixed doses according to international guidelines [11]. Unfortunately, evidence supporting this assumption is scarce and mainly related to specific groups of patients [12][13][14][15] or antifungal class [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%